The Mediating Effect of Perceived Social Acknowledgment on the Relationship Between Patient Assaults and Posttraumatic Stress Reactions in Emergency Nurses. Issue 18 (September 2019) - Guan, Ruiyuan; Gao, Jun; Liu, Guangzhi; Cheng, Fei; Ge, Baolan
This study explored whether posttraumatic stress symptoms resulted from workplace assaults were mediated by the perception of social acknowledgment by the victim. A sample of 444 emergency room nurses in China completed questionnaires measuring the frequency and types of patient assaults, the severity of physical injury, the perception of social acknowledgment, and the posttraumatic stress symptoms. Cross-sectional design, multiregression, and bootstrapping mediation analyses were used to test the hypotheses. Results showed that general disapproval and family disapproval mediated the relationship between the frequency of patient assaults and the severity of posttraumatic stress symptoms. These two factors also mediated the links between the injury severity of patient assaults and the development of posttraumatic stress symptoms. Implications for clinical practice and future research were discussed.